2021
DOI: 10.1002/adfm.202110828
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Water‐Assisted Additional Capacity for Nickel Hydroxide Anode Materials

Abstract: To further increase the energy density of rechargeable batteries to meet the rapidly growing needs of high-energy consuming devices, various materials are tested as anode materials. Some of these newly developed anode materials exhibit anomalously high capacities that exceed their theoretical values. Advanced analytical techniques have revealed that unconventional reaction mechanisms account for these extra capacities. However, despite the potential to take current battery technology development to the next le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…1f show lattice fringes corresponding to (100), (101), and (002) planes of Ni(OH) 2 and (110) plane of Ni 3 Si 2 O 5 (OH) 4 . 30,31 These results reveal the coexistence of Ni(OH) 2 and Ni 3 Si 2 O 5 (OH) 4 in the surface nanosheets of NiSiC.…”
Section: Resultsmentioning
confidence: 72%
“…1f show lattice fringes corresponding to (100), (101), and (002) planes of Ni(OH) 2 and (110) plane of Ni 3 Si 2 O 5 (OH) 4 . 30,31 These results reveal the coexistence of Ni(OH) 2 and Ni 3 Si 2 O 5 (OH) 4 in the surface nanosheets of NiSiC.…”
Section: Resultsmentioning
confidence: 72%
“…5, the peaks at ~2.20 V in anodic scan and ~1.25 V correspond to the conver-sion reaction. Other peaks from the reaction of the LiOH phase appeared at relatively low potentials, which are marked in the blue region [7,17,38]. Notably, the intensity of the peaks from the conversion and LiOH reactions in the CV curve of Co(OH) 2 / GNP is larger than that of bare Co(OH) 2 , which represents a greater contribution of the two reactions in the composite material.…”
Section: Resultsmentioning
confidence: 97%
“…The minor changes in the Co K-edge position in the low-potential region indicate that the reversible capacity in the low-potential range did not originate from the conversion reaction. It has been reported that, in this potential region, the LiOH phase formed by the conversion reaction of transition metal hydroxides additionally reacts with lithium, delivering a large additional capacity [7,17,18]. Therefore, the large capacity in the low potential range during charging in Co(OH) 2 /GNP is ascribed to the high contribution of the reversible reaction of LiOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that there are two forms of layered nickel hydroxide (aand b-Ni(OH) 2 ). [30][31][32][33][34][35] The a-Ni(OH) 2 is not stable in an alkaline media and transforms into the b-Ni(OH) 2 . [34][35][36][37][38][39] Therefore, it is essential to synthesize b-Ni(OH) 2 with a reduced number of layers in each b-Ni(OH) 2 nanoparticles for a high SC.…”
Section: Introductionmentioning
confidence: 99%